KEMAMPUAN MEMBEDAKAN ANTARA KOSAKATA BAKU DAN KOKATA TIDAK BAKU BAGI SISWA KELAS XII IPS SMA NEGERI 7 PINRANG: THE ABILITY TO DISTINGUISH BETWEEN STANDARDISED AND NON-STANDARDISED VOCABULARY FOR STUDENTS IN CLASS XII IPS SENIOR HIGH SCHOOL 7 PINRANG - Adil Ryadi, Rahmat; Mayong; Jahrir, Andi Sahtiani (Journal of Applied Linguistics and Literature, 2023)
This study aims to describe the level of ability of class XII IPS students at SMA Negeri 7 Pinrang in differentiating standard vocabulary from non-standard vocabulary. This type of research is quantitative research using a research design based on statistical procedures. The population of this study were all students of class XII IPS at SMAN 7 Pinrang, consisting of three classes with a total of 104 people. The sample for this research was 34 students from class XII IPS. The sample was selected using Random Sampling Technique. Data collection was carried out using test techniques with the form of objective tests. The results of data analysis show that students' mastery in answering questions with standard vocabulary and non-standard vocabulary is 53% in the poor category. Therefore, class XII IPS students at SMA Negeri 7 Pinrang are categorized as less able to differentiate standard vocabulary from non-standard vocabulary based on the KBBI.